Millimeter-scale radioluminescent power for electronic sensors - Averal N. Kandala; Sinan Wang; Joseph E. Blecha; Yung-Hua Wang; Rahul K. Lall; Ali M. Niknejad; Youngho Seo; Michael J. Evans; Robert R. Flavell; Henry F. VanBrocklin; Mekhail Anwar (iScience)
Summary: The storage and generation of electrical energy at the mm-scale is a core roadblock to realizing many untethered miniature systems, including industrial, environmental, and medically implanted sensors. We describe the potential to address the sensor energy requirement in a two-step process by first converting alpha radiation into light, which can then be translated into electrical power through a photovoltaic harvester circuit protected by a clear sealant. Different phosphorescent and scintillating materials were mixed with the alpha-emitter Th-227, and the conversion efficiency of europium-doped yttrium oxide was the highest at around 2%. Measurements of the light generated by this phosphor when combined with Th-227 reveal that over 100 nW of optical power can be expected at volumes around 1 mm3 over more than two months. The use of a clear sealant, together with the evaporation of liquid solution following the mixture, can enable safe miniaturization for size-constrained medical and internet-of-things (IoT) sensor applications.